2014
DOI: 10.4155/tde.14.77
|View full text |Cite
|
Sign up to set email alerts
|

Caffeic Acid Loading Wound Dressing: Physicochemical and Biological Characterization

Abstract: The hydrogels obtained could be useful as caffeic acid delivery-system devices for the treatment of wound infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 16 publications
(46 citation statements)
references
References 26 publications
4
42
0
Order By: Relevance
“…The following peaks were identified on the HPMC spectrum: 3442 cm −1 (O‐H stretching), 2936 cm −1 (stretching vibrational asymmetric of C‐H), 1652 cm −1 (hydrogen interactions), and 1060 cm −1 (ether bond). The stronger intensity peaks observed for the HPβCD were 3440 cm −1 (O‐H stretching), 2930 cm −1 (stretching vibrational asymmetric of C‐H), 1640 cm −1 (hydrogen interactions), 1115 cm −1 (C‐O stretching) and 1040 cm −1 (C‐O‐C) . The hydrogels spectra were identical and it was possible to confirm the formation of intermolecular bounds between the monomers.…”
Section: Resultsmentioning
confidence: 74%
See 3 more Smart Citations
“…The following peaks were identified on the HPMC spectrum: 3442 cm −1 (O‐H stretching), 2936 cm −1 (stretching vibrational asymmetric of C‐H), 1652 cm −1 (hydrogen interactions), and 1060 cm −1 (ether bond). The stronger intensity peaks observed for the HPβCD were 3440 cm −1 (O‐H stretching), 2930 cm −1 (stretching vibrational asymmetric of C‐H), 1640 cm −1 (hydrogen interactions), 1115 cm −1 (C‐O stretching) and 1040 cm −1 (C‐O‐C) . The hydrogels spectra were identical and it was possible to confirm the formation of intermolecular bounds between the monomers.…”
Section: Resultsmentioning
confidence: 74%
“…The hydrogels were obtained thought the crosslinking of HPMC, HPβCD and CS. Cyclodextrins based hydrogels using HPMC and HPβCD, crosslinking with BDGE, were successfully obtained by Pinho et al The materials showed suitable properties for drug delivery and wound treatment . In the present work, CS was used to introduce a new feature to the hydrogel, pH‐sensitivity.…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…Antimicrobial wound dressings have been often used to protect the wound from new injury, dehydration, and microorganism deposition . Several materials (textiles, hydrogels, foams, and films) have been developed to deliver antimicrobial agents to infected wounds . Although, they still show inadequate release profile, characterized by an initial burst that leads to local toxicity owed high antimicrobial concentration, followed by a prolonged release of antimicrobial agent below required concentration, selecting the resistant microorganisms …”
Section: Introductionmentioning
confidence: 99%